2019
DOI: 10.3390/toxins11020102
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Ear Damage of Helicoverpa zea on Transgenic Bacillus thuringiensis Maize in the Field in Texas, U.S. and Its Susceptibility to Vip3A Protein

Abstract: The corn earworm, Helicoverpa zea (Boddie), is a major pest of Bacillus thuringiensis (Bt) maize and cotton in the U.S.. Reduced efficacy of Bt plants expressing Cry1 and Cry2 against H. zea has been reported in some areas of the U.S.. In this study, we evaluated the occurrence and ear damage of H. zea on transgenic Bt maize expressing Cry proteins or a combination of Vip3A and Cry proteins in the field in Texas in 2018. We found that the occurrence of H. zea larvae and the viable kernel damage area on the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
148
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(154 citation statements)
references
References 37 publications
5
148
0
1
Order By: Relevance
“…Therefore, we used 3.0 μg/cm 2 Vip3Aa39 as the diagnostic concentration for the F 2 screens. Susceptibility to Vip3Aa39 of the F 2 families of H. zea was evaluated using a diet-overlay bioassay as described in Yang et al 15 . Briefly, 0.8 ml of liquid diet (Southland Product, Inc. Lake Village, AR) was dispensed using repeater pipets into each well of 128-well bioassay trays (C-D International, Pitman, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we used 3.0 μg/cm 2 Vip3Aa39 as the diagnostic concentration for the F 2 screens. Susceptibility to Vip3Aa39 of the F 2 families of H. zea was evaluated using a diet-overlay bioassay as described in Yang et al 15 . Briefly, 0.8 ml of liquid diet (Southland Product, Inc. Lake Village, AR) was dispensed using repeater pipets into each well of 128-well bioassay trays (C-D International, Pitman, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, field-evolved resistance of H. zea to Cry1 and Cry2 proteins has been widely reported in the U.S., especially in the Southern states 15,[18][19][20][21] . For example, Yang et al 15 and Kaur et al 21 documented field-evolved practical resistance of H. zea populations in Texas and Louisiana to Cry1A.105/Cry2Ab2 corn, respectively. In 2018, Reisig et al 19 reported field-evolved practical resistance of H. zea to Bt cotton containing Cry1Ac/Cry1F and Cry1Ac/ Cry2Ab proteins in North Carolina.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that the 15bp insertion, which produces a DNTAT amino acid sequence in GA-R, is present in the reference genome. The strain of H. zea used for genome sequencing was described as highly susceptible to Cry1A toxins by Pearce et al (2017), which is true relative to levels of resistance recently described in H. zea (Brévault et al, 2013; Dively et al, 2016; Reisig et al, 2018; Yang et al, 2019). Yet in the early 1990s, before Bt crops were commercialized, this long-term laboratory-reared strain was less susceptible to Cry1Ac than most strains derived recently from the field, including a >400-fold difference in one case (Luttrell et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Helicoverpa zea is one lepidopteran species targeted by Bt crops with low susceptibility to Cry proteins (Stone and Sims, 1993; Ali et al, 2006; Sivasupramaniam et al, 2008). A major pest of both corn and cotton in the U.S., H. zea has evolved resistance to several Cry proteins (Welch et al, 2015; Dively et al, 2016; Reisig et al, 2018; Kaur et al, 2019; Yang et al, 2019). While some efforts have been made to understand the molecular mechanisms underlying Cry resistance in H. zea (Caccia et al, 2012; Zhang et al, 2019), we still know little about how selection by Cry proteins has shaped genotype frequencies in this important pest.…”
Section: Introductionmentioning
confidence: 99%